Qiraat Shadhdhah in Deriving Legal Rulings of the Hanafi and Shafii Schools of Jurisprudence - Muhammad Mukmin Alhafiz Zahari; Sabri Mohamad (Rabbanica: Journal of Revealed Knowledge)
Qiraat Shadhdhah is a recitation that does not meet the standards and criteria agreed upon by Islamic scholars. This type of recitation does not fulfill any or all of the three criteria for accepting Qiraat Mutawatirah, namely a valid chain of transmission (sanad), conformity with Arabic language rules, and conformity with one of the 'Uthmani codices. Although this recitation is not recognised as the Quran, its acceptance as one of the sources for legal reasoning in fiqh issues is a subject of dispute and debate among fiqh mazhab. Therefore, this article discussed the status and role of Qiraat Shadhdhah in legal reasoning in fiqh. This study focuses on the opinions of the Hanafi and Shafii schools only. The research uses a qualitative method, while data collection is conducted through a literature review. The study found that Qiraat Shadhdhah is an essential source in the legal reasoning of fiqh scholars when determining the ruling on a matter. This importance is evident when some narrations of Qiraat Shadhdhah are still used in fiqh scholars' discussions, even though those recitations have been abrogated.